2019
DOI: 10.3390/ijerph16203968
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction with Rural Medical Services: A Cross-Sectional Survey in 11 Western Provinces in China

Abstract: Rural medical services play an important role in protecting and promoting the health of the rural population; however, patient satisfaction with rural medical services has been understudied in China. A better understanding of the actual situation and the determinants involved will provide evidence for health-related policy makers and hospital managers to further improve rural medical services. A total of 9811 patients (5208 outpatients and 4603 inpatients) were included in this study from a cross-sectional sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
37
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 47 publications
7
37
2
1
Order By: Relevance
“…The level of patient satisfaction (60.5%) in our study was higher than the results obtained in other areas either in China or elsewhere, such as in Taiwan (35%) 39 Malaysia 22 and 11 western provinces in China (60%) 40 ; however, it was lower than that in Shandong, 41 Jiangxi 42 and other cities in Gansu, China, 33 43 and also in Spain 44 and Australia. 45 This might have been related to differences in sample size, region and the use of a different survey scale.…”
Section: Discussioncontrasting
confidence: 78%
“…The level of patient satisfaction (60.5%) in our study was higher than the results obtained in other areas either in China or elsewhere, such as in Taiwan (35%) 39 Malaysia 22 and 11 western provinces in China (60%) 40 ; however, it was lower than that in Shandong, 41 Jiangxi 42 and other cities in Gansu, China, 33 43 and also in Spain 44 and Australia. 45 This might have been related to differences in sample size, region and the use of a different survey scale.…”
Section: Discussioncontrasting
confidence: 78%
“…Compared with those who were ≤35 years, residents who were ≥46 years were 1.33 times more likely to be satisfied with rural BPHSs. The potential explanations include that the attitudes of PHC workers might be better toward the relatively older residents and these residents might have a lower expectation of BPHSs [21]. However, in terms of other characteristic indicators, i.e., gender, education, occupation, monthly income, and health status, there was no significant association between them and overall satisfaction with rural BPHSs.…”
Section: Discussionmentioning
confidence: 93%
“…These results suggest that besides BPHSs' items, rural patients also care a lot about PHC worker attitudes, from which they might feel respect, politeness, etc. [21].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported positive results, while some studies indicated that a negative or no relationship exists between SDM and health outcomes [27]. Because physician services represent a basic concern in medical care, medical expenses still impose a great nancial challenge to patients, and patients are the least satis ed with medical expenses [28]. Treatment outcomes affect patients' health and quality of life; thus, determining whether a high level of SDM speci cally leads to better patient perceptions of physician services, medical expenses and treatment outcomes is warranted.…”
Section: Introductionmentioning
confidence: 99%